1991
DOI: 10.1002/arch.940180405
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity studies on adipokinetic hormones in Manduca sexta

Abstract: Structure-activity studies were performed for adipokinetic hormone (AKH) in Manduca sexta. Seven naturally occurring and four synthetic peptides of the red pigment concentrating hormone (RPCH)/AKH family were tested in larvae of M. sexta for activation of glycogen phosphorylase in fat body. pGlu at the N-terminal was found to be important for activity of peptides; however, Manduca AcGly1AKH is partially active. The amino acids at all positions appear to be of importance for activity, with the possible exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…The ED50 value for the activation of fat body glycogen phosphorylase by Manducu AKH was approximately 30 fmol peptide per abdomen and 2 pmol was the smallest amount which induced maximum activation of phosphorylase, i.e., 80% of the enzyme were in the active form (data not shown). These results are in very good agreement with those published by Ziegler and coworkers [3,15,16].…”
Section: Activation Of Fat Body Glycogen Phosphorylasesupporting
confidence: 95%
“…The ED50 value for the activation of fat body glycogen phosphorylase by Manducu AKH was approximately 30 fmol peptide per abdomen and 2 pmol was the smallest amount which induced maximum activation of phosphorylase, i.e., 80% of the enzyme were in the active form (data not shown). These results are in very good agreement with those published by Ziegler and coworkers [3,15,16].…”
Section: Activation Of Fat Body Glycogen Phosphorylasesupporting
confidence: 95%
“…This finding is in agreement with an in vitro SAR study of the D. melanogaster AKHR (Caers et al, 2012). In vivo studies also showed that a functional response still occurred when the blocked N-termini of P. americana, L. migratoria and M. sexta AKH peptides were replaced by other residues (G€ ade and Hayes, 1995;Goldsworthy et al, 1997;Lee et al, 1997;Ziegler et al, 1991). A ligand-docking model of the Anoga-AKH peptide with its cognate receptor confirms the suggestion that neither the N-nor the Cterminus interacts with the Anoga-AKHR (Mugumbate et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Previous work had mostly also reported lower activity when the pGlu was replaced by other blocked amino acids [9,17,29,41,42]. In fact, a severe loss of binding was recorded in in vitro receptor binding assays with an N-terminal acetylated-Ala analog of the fruit fly AKH [5], which also points to a change in accessibility of the ligand to the expressed receptor.…”
Section: Chain Length Of Akhsmentioning
confidence: 93%